Legal Certainty of Cabotage Principle Regarding Sea Transportation in Indonesia - Annalisa Y; Murzal Murzal; Rizka Nurliyantika (Sriwijaya Law Review, 2021)
Shipping between domestic ports must be transported by ships with Indonesian flags and operated by national shipping companies, meaning the cabotage principle. The aim is to prevent and reduce dependence on foreign ships carrying out Indonesia's maritime territory. However, in regulating and implementing the cabotage principle, it is not sure that it can be applied absolutely, which can be interpreted as not reflecting legal certainty. This study aims to analyze the legal certainty of implementation of the cabotage principle in Indonesian territorial waters. This research is a normative study that uses legal, historical, interpretation and case approaches. The case and interpretation approaches are used to examine the cabotage principle concept in legislation and several relevant cases brought to Indonesian courts. The results shows that the regulation of the cabotage principle on sea transportation is found in the form of laws, presidential regulations, presidential instructions and ministerial regulations. However, in other various regulations, the cabotage principle does not apply absolutely (semi-protectionist) or inconsequently. On the one hand, this is because it prohibits foreign ships from operating in Indonesian territory to carry passengers and/or goods between islands or ports. On the other hand, foreign ships are allowed for other activities that do not include carrying passengers and/or goods with certain conditions and approval from the government. The application of the cabotage principle based on judges' considerations in cases submitted to the State Administrative, Supreme and the Constitutional Courts has fulfilled legal certainty according to the Shipping Law. However, the protection of national Shipping must be prioritized, and the use of foreign ships should be considerably tightened unless Indonesian-flagged vessels are not insufficiently available.